A patient with a novel CNTNAP2 homozygous variant: further delineation of the CASPR2 deficiency syndrome and review of the literature. Issue 2 (April 2019) - Riccardi, Florence; Urquhart, Jill; McCullagh, Gary; Lawrence, Peter; Douzgou, Sofia
Abstract : Supplemental Digital Content is available in the text.